Analysis of the epidemiological profile of interactions for cardiac insufficiency in the municipality of Teresina-PI (Research, Society and Development, 2020)
To analyze the epidemiological profile of hospitalizations due to heart failure in the city of Teresina, Piauí, from 2011 to 2015. This is a descriptive, quantitative and retrospective study, with secondary data collection performed in the Department of Information Technology of the Single System of Health (DATASUS). There was a decrease in the number of hospitalizations between 2011 and 2015, predominantly male (56.2%), the age group between 70 and 79 years (23.4%), related to skin color, a large part did not register the variable, but of those that had, the color predominated (92.3%). Heart failure in Teresina-PI occurs with a higher prevalence in the elderly, with individuals over 60 years of age, of brown skin color, male and before the analysis per year, a tendency to reduce hospitalizations is observed, indicating which strategies of the primary level of health have had effect.